Estratégias adotadas para adesão de pacientes diabéticos na atenção primária à saúde: revisão integrativa da literatura - SANTA ROSA, Brenda de Oliveira (2024)
INTRODUCTION: Diabetes mellitus is a chronic and non-transferable disease, classified as the third cause of deaths in the Brazilian population. The diagnosis is made, mostly times, in a belated way increasing the risk of complications. Another factor which contributes to a negative prognosis of this illness is the low tack to the pharmacological treatment. OBJECTIVE: the aim is identify strategies to the pharmacological treatment adoption from diabetics patients on primary health care. MATERIALS AND METHODS: This research may be categorized as a literature review, using four databases: Web of Science, SciELO, Science Direct and LILACS in order to select articles, as well a valid instrument.The content analysis from Laurence Bardin is divided in three moments: pre analysis, material exploration, discussion of results and interpretation. After obtaining the corpus, was used thematic analysis, proposing categorizing the most highlighted themes among the studies and talking about them. RESULTS: The main objective of the strategies was to encourage self-care and empowerment of diabetic patients. Intervention strategies included collective meetings, creation of goals or action plans, nursing consultations and telephone calls. FINAL CONSIDERATIONS: It is concluded that despite the limitations encountered, it was possible to identify effective forms of strategies used in PHC that contributed to increased adherence to pharmacological treatment of diabetic patients.